Company Valuation Of PT. Bank ABC To Prepare Acquisition Strategy (The Indonesian Journal of Business Administration, 2021)
OJK has made POJK R Number 12 / POJK.03 / 2020 concerning the minimum capital adequacy regulation for each bank. Bank ABC is a bank with tier 1 of less than IDR 1 billion. The next step is for Bank ABC to conduct a valuation of the company to find out the company valuation of Bank ABC when there will be additional of shares in the future. After knowing and company valuation from Bank ABC, a corporate action recommendation will be generated that must be carried out by Bank ABC implementation planning steps is acquisition. In a business situation, the insufficiency of Bank ABC's core capital is constrained by external political factors (POJK No.12 / POJK.03 / 2020) which make ABC Bank unable to develop (up to become Book Bank II), especially in terms of developing digital services to respond to external factors challenges technology. The analytical method used in this research is case study analysis with ratio assessment, financial performance analysis and company assessment using Discounted Cash Flow (DCF) approach. With assuming a discount rate of 12% and a time period for the next 5 years with an average terminal value shows that the market equity value / share calculation is IDR 350.000,- while intrinsically it is IDR 1.349.240,- so the target price per share is 2.85x from the initial share price. CKPN increases by approximately 40%. Where deposits are the largest expense that must be paid by Bank ABC when compared to Giro and Savings. The conclusion if Bank ABC want to take acquisisioned, Bank ABC can give the equity price / share at the IDR. 1.349.240,- / share or 2.85x from the initial price/share. Then after the acquisition process Bank ABC must take the improvement strategy at the quality of Loans and recompositioning proportion at short term liabilities especially at the Deposito.Key Words: Banking, acquisition, valuation, discounted cash flow, Financial performance analysis.